Protein engineering and plants: the evolution of sustainable agriculture. (10th March 2023) - Wright, R. Clay; Neres, Deisiany Ferreira; Chaisupa, Patarasuda; Bryant, John A.
Abstract : Humanity is faced with an enormous challenge in the coming decades. The world's population is rapidly growing and we need to produce enough food, fuel, medicine and goods to support this growth in an environmentally sustainable and restorative way. Plants will inevitably provide many solutions to the problems we face, but we need to build environmentally sustainable, carbon-negative industries as soon as possible. Applying protein engineering to accelerate the development of improved crop varieties that can produce more while using less is a promising approach. Here we provide an introduction to the approaches, tools and philosophy of protein engineering, as well as several examples of problems in plant breeding and engineering that protein engineers are currently working to solve.